Role of E- commerce Providers’ Strategy on Increase of the Online Shops Growth (A Case of Indonesian Ecommerce during the Digital Age) - Jusuf, Dewi Indriani; Sarwono, Jonathan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The aim of the research is to know the role of e- commerce providers’ strategy on increase of the online shops growth in Indonesia. The method used is systematic secondary data search and meta analysis. This study finds the following matters concerning to Indonesian major e-commerce platform providers: First, there are five popular means of online advertisement, namely search engine, social media, comment, web site and compared price. Second, the most effective digital advertising channels to reach consumers are search engines, such as Google. Third, the most popular social media usage is TikTok and Instagram. Fourth, the most effective social commerce strategies are as follows: a) Interactive Content; b) Influencer Marketing; c) User-Generated Content; d) Social Proof; e) Special Promotions. Fifth, the emerging e-commerce trends in 2024: a) increased use of livestream commerce as a primary sales channel; b) marketing strategies that leverage data analytics to improve customer experiences. Sixth, each of ecommerce provider has superior features. Seventh, number of visitors of the major ecommerce providers get more and more visitors. Eight, type of products that have been purchased by the consumers vary from small things, such as accessories, electronic goods up to home equipment. Ninth, the advantage of the online purchase for the consumers is that they can compare the prices of products and get the cheaper price. Tenth, the payment method used by the online consumers can be summarized into two ways, namely prepaid and postpaid payment.